2016
DOI: 10.1039/c6cc04575h
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of nitrotyrosine-containing proteins using an aniline-based oxidative coupling strategy

Abstract: A convenient two-step method is described for the detection of nitrotyrosine-containing proteins. First, nitrotyrosines are reduced to aminophenols using sodium dithionite. Following this, an oxidative coupling reaction is used to attach anilines bearing fluorescence reporters or affinity probes. Features of this approach include fast reaction times, pmol-level sensitivity, and excellent chemoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Combining the results from each method allowed unequivocal separation of the modified site from other potentially reactive residues, and the site of the +15 Da modification was confirmed as Y115 (Figure ). By comparison, MS analysis of RNase A modified in solution (using the small nitrating agent tetranitromethane (TNM), and subsequent reduction) was shown to give the 4x modified protein as the major product (Supporting Information, Section 10); further confirming that the observed Tyr residue selectivity could be attributed to the catch‐and‐release approach.…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…Combining the results from each method allowed unequivocal separation of the modified site from other potentially reactive residues, and the site of the +15 Da modification was confirmed as Y115 (Figure ). By comparison, MS analysis of RNase A modified in solution (using the small nitrating agent tetranitromethane (TNM), and subsequent reduction) was shown to give the 4x modified protein as the major product (Supporting Information, Section 10); further confirming that the observed Tyr residue selectivity could be attributed to the catch‐and‐release approach.…”
Section: Methodsmentioning
confidence: 85%
“…To demonstrate the utility of the o ‐aminophenol modification, a fluorophore was conjugated to the catch‐and‐release modified RNase A using an oxidative coupling strategy developed by Francis et al . (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…The cpTMV disks containing ncAAs were then subjected to potassium ferricyanide-mediated oxidative coupling conditions as previously reported by our laboratory for p AF- and 3NY-containing proteins (Figure a). The accessibility of the mutated amino acids in the cpTMV-S65- p AF and -3NY constructs was first examined through small-molecule couplings. For the 3NY mutant, treatment with sodium dithionite was first required to reduce the nitrophenol to an aminophenol, producing cpTMV-S65-3-aminophenol (cpTMV-S65-3AY).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, the PTN level in the biological samples was observed up to nanomole level and has significant differences among different samples (plasma, urine or tissue) . In addition, the nitration in tyrosine usually occurs in different kinds of proteins.…”
Section: Methodsmentioning
confidence: 96%